Re-Reading Luke 10:25-37 in the Digital Age: Postcolonial Exegesis and Filipino Perspectives on Cyber-Neighborliness - Jacoba, Rico (Media: Jurnal Filsafat dan Teologi, 2025)
This article reinterprets the Parable of the Good Samaritan (Luke 10:25–37) through a triadic approach integrating postcolonial exegesis, Filipino cultural hermeneutics, and digital theology. It revisits the question “Who is my neighbor?” within the context of cyberspace, employing the Filipino concepts of kapwa and pakikipagkapwa-tao as ethical foundations for solidarity that transcends geographical and social boundaries. Through postcolonial analysis, the study exposes the power dynamics embedded in traditional interpretations and demonstrates how digital theology enables new expressions of compassion in online spaces. The findings reveal that digital platforms can function as modern “roads to Jericho,” where inclusion, exclusion, and advocacy unfold. By integrating theological and cultural insights, the study asserts that neighborliness is not merely a moral gesture but a theological vocation to embody mercy and justice within digital networks. It concludes that kapwa offers a humanistic and contextually grounded framework for digital ethics, calling the Church and society to cultivate genuine fraternity in cyberspace as an extension of Christian compassion and mission.